DOING RIGHT ON JOINT VOE-FINANCIAL INSTITUTION TAXATION: HOW GOOD IS YOUR ACCOUNTING? - Yasni, Raynal; Kuncoro, Antonius Ragil (Jurnal Aplikasi Akuntansi, 2025)
Tax Compliance of Joint Village Owned Enterprise-Financial Institution (Joint VoE-FI) requires assistance, considering that this institution has been just established for about two years as a mandate from Government Regulation (PP) Number 11 of 2021. There has been a significant transformation in the management of Joint VoE-FI from a general government into a business entity. Consequently, it will face fiscal risk in the future. This research analyzes how this institution completes tax obligations under limited human resources and how efforts are made to maintain its tax compliance. The narrative research approach, as explained by Elliott (2005), is used to organize a sequence of field events into a whole so that the significance of each event can be understood through its relation to that whole, which is supported by direct observation data on objects, interviews, and document reviews. The research results show that assistance for business entities in fulfilling tax obligations is necessary, considering that human resources in villages still need to be improved. These findings have real-world implications. First, Professionals working in Joint VoE-FIs should continue to invest in their skills and training. Second, policymakers should focus on increasing the capacity of Joint VoE-FIs by providing continuous support through training and educational programs.